Zatanna : the jewel of Gravesend - Arden, Alys (DC graphic novels for young adults., 2022)
Zatanna lives happily in Coney Island until a mystic's quest for a powerful jewel unravels everything she thought she knew about herself, her family's legacy, and her beloved neighborhood.